Laser sintering of nano-hydroxyapatite coated polyamide 12 powders - Hui, D.; Goodridge, R.D.; Scotchford, C.A.; Grant, D.M. (Elsevier, 2018)
As part of a larger study on the laser sintering (LS) of nano-composite structures for biomedical applications, a wet mixing method was used to coat Polyamide 12 (PA12) particles with nano-hydroxyapatite (nHA). The addition of nHA significantly affected powder processability due to laser absorption and heat transfer effects which led to part warping. This phenomenon has not been reported in other studies investigating LS of polymer/HA and nHA powders. Nano-composites containing 0.5–1.5 wt% nHA were successfully produced and tensile testing showed that 0.5 wt% nHA provided the greatest reinforcement with a 20% and 15% increase in modulus and strength respectively. However, the elongation at break had significantly declined which was likely due to the formation of nHA aggregates at the sintering borders following the processing of the coated powders despite being initially well dispersed on the particle surface.